Insights into the Indian Peanut Genotypes for ahFAD2 Gene Polymorphism Regulating Its Oleic and Linoleic Acid Fluxes - Nawade, Bhagwat; Bosamia, Tejas C.; Thankappan, Radhakrishnan; Rathnakumar, Arulthambi L.; Kumar, Abhay; Dobaria, Jentilal R.; Kundu, Rahul; Mishra, Gyan P. (Frontiers in Plant Science, 2016)
In peanut (Arachis hypogaea L.), the customization of fatty acid profile is an evolving area to fulfil the nutritional needs in the modern market. A total of 174 peanut genotypes, including 167 Indian cultivars, 6 advanced breeding lines and ‘SunOleic’‒ a double mutant line, were investigated using AS-PCRs, CAPS and gene sequencing for the ahFAD2 allele polymorphism, along with its fatty acid compositions. Of these, 80 genotypes were found having substitution (448G>A) mutation only in ahFAD2A gene, while none recorded 1-bp insertion (441_442insA) mutation in ahFAD2B gene. Moreover, 22 wild peanut accessions found lacking both the mutations. Among botanical types, the ahFAD2A mutation was more frequent in ssp. hypogaea (89%) than in ssp. fastigiata (17%). This single allele mutation, found affecting not only oleic to linoleic acid fluxes, but also the composition of other fatty acids in the genotypes studied. Repeated use of a few selected genotypes in the Indian varietal development programs were also eminently reflected in its ahFAD2 allele polymorphism. Absence of known mutations in the wild-relatives indicated the possible origin of these mutations, after the allotetraploidization of cultivated peanut. The SNP analysis of both ahFAD2A and ahFAD2B genes, revealed haplotype diversity of 1.05% and 0.95%, while Ka/Ks ratio of 0.36 and 0.39 respectively, indicating strong purifying selection pressure on these genes. Cluster analysis, using ahFAD2 gene SNPs, showed presence of both mutant and non-mutant genotypes in the same cluster, which might be due the presence of ahFAD2 gene families. This investigation provided insights into the large number of Indian peanut genotypes, covering various aspects related to O/L flux regulation and ahFAD2 gene polymorphism.